2014
DOI: 10.1186/bcr3685
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of personalized peptide vaccination for metastatic recurrent triple-negative breast cancer patients

Abstract: IntroductionSince treatment modalities for metastatic recurrent triple-negative breast cancer (mrTNBC) are limited, a novel treatment approach including immunotherapy is required. We have developed a novel regimen of personalized peptide vaccination (PPV), in which vaccine antigens are individually selected from a pool of different peptide candidates based on the pre-existing host immunity. Herein we conducted a phase II study of PPV for metastatic recurrent breast cancer patients to investigate the feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…The research investigating clinical biomarkers related to immunologic factors or TILs involving EBC is still insufficient. Our previous studies showed that the expression of FOXP3 on lymphocytes or tumor cells of EBC was significantly associated with clinical outcome and tumor‐specific immune responses, as well as the observation that clinical benefits in patients with metastatic BC could be augmented by peptide vaccines derived from various tumor‐associated antigens . In this study, we described the tumor environmental interaction between the density of TILs or macrophages and various immunologic molecules, including PD‐L1, PD‐1, and PTEN, by the intrinsic biological subtypes in EBC.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The research investigating clinical biomarkers related to immunologic factors or TILs involving EBC is still insufficient. Our previous studies showed that the expression of FOXP3 on lymphocytes or tumor cells of EBC was significantly associated with clinical outcome and tumor‐specific immune responses, as well as the observation that clinical benefits in patients with metastatic BC could be augmented by peptide vaccines derived from various tumor‐associated antigens . In this study, we described the tumor environmental interaction between the density of TILs or macrophages and various immunologic molecules, including PD‐L1, PD‐1, and PTEN, by the intrinsic biological subtypes in EBC.…”
Section: Discussionmentioning
confidence: 80%
“…Breast cancer is traditionally thought of as a kind of low immunogenic carcinoma, but the influence of local immunologic factors on clinical outcome of BC is still under evaluation. It has been indicated that FOXP3 expression on lymphocytes and tumor cells of EBC is significantly associated with clinical outcome and that the peptide vaccines of tumor‐associated antigens could induce and boost tumor‐specific immune response in patients with metastatic BC . Novel investigations have shown that immunologic factors, such as TILs, and immune relevant factors, including PD‐1, PD‐L1, and PTEN, are significantly associated with responses to treatment and clinical outcome .…”
mentioning
confidence: 99%
“…Early trials in multiple different tumor types have shown a response rate of 9.9% and a disease control rate of 42.9% in a group of 500 patients with advanced cancer [70]. PPV has been evaluated in TNBC and was safe and potentially effective, with a median PFS of 7.5 months and median OS of 11.1 months in metastatic TNBC, with 1 complete response and 1 partial response noted in a cohort of 18 patients [71]. Additional small studies are ongoing in TNBC (NCT02427581).…”
Section: Vaccinesmentioning
confidence: 99%
“…Notably, the immune status of patients can influence its clinical course [3]. For instance, decreased infiltration of CD8 + cytotoxic T-lymphocytes (CTLs) in tumor has been associated with lymph node metastasis and poor response to neoadjuvant chemotherapy [46], while the activation of immune responses has been related to improved overall survival in patients with breast cancer [7]. Thus, an anti-cancer immune status is thought to be important for preventing cancer recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%